Thermostable amidase catalyzed production of isonicotinic acid from isonicotinamide. Issue 9 (September 2015) - Mehta, Praveen Kumar; Bhatia, Shashi Kant; Bhatia, Ravi Kant; Bhalla, Tek Chand
Graphical abstract: Highlights: Biotransformation of isonicotinamide to isonicotinic acid at 1 L fed batch scale. Different process parameters were optimized for production of isonicotinic acid. Amidase of G. subterraneus RL-2a showed superior operational thermostability. Isonicotinic acid was produced (61.55 g) at a rate of 1.18 g h −1  g dcw −1 . Abstract: The biotransformation of isonicotinamide was investigated using thermophilic intracellular amidase produced from Geobacillus subterraneus RL-2a. Various process parameters, including amount of biocatalyst, substrate feeding rate, enzyme-to-substrate ratio and operational thermostability were systematically examined with the aim of achieving complete substrate conversion and high productivity. In 1 L fed batch reaction containing 0.1 M isonicotinamide, in 0.2 M potassium phosphate buffer (pH 6.5, 200 rpm) and 8 U ml −1 amidase activity (12.48 mg dcw ml −1 ) of whole cells of G. subterraneus RL-2a (as biocatalyst) resulted in a yield of 0.1 M of isonicotinic acid after 50 min reaction time at 70 °C and a total of 61.55 g isonicotinic acid was produced at a rate of 1.18 g h −1  g −1  dcw respectively. The volumetric productivity was 14.8 g h −1  l −1 .